Fillet flap method of ear keloid repair and its cosmetic outcome: our experience - G., Rajalakshmi; Arif, Mohammed; M., Sanjana (International Surgery Journal, 2017)
Background: Formation of keloid after cosmetic or traditional ear piercing is a very distressing condition for the patient. Ear lobe keloid has been treated with excision followed by primary suture, healing by secondary intention, skin graft or local flap. Fillet flap technique has come up with good cosmetic result, late combined with other medications. Methods: 20 patients were treated by fillet flap technique. Included in the study were huge, sessile, recurrent keloids. Pedunculated and small (<1 cm) keloids were excluded. Results: All cases, except one flap survived completely with good primary healing. All patients were women and developed their lesions after cosmetic earlobe piercing. The lesions were unilateral in 16 (80%) patients and bilateral in four (20%) patients. After 1 year, major response was observed in fifteen cases (75%) and moderate response in four cases (20%); one case had a relapse 10 months after the surgery. Conclusions: Many methods of coverage of defect after surgical excision have been described but each has its own disadvantages. So, fillet flap technique covers the defect and gives very good cosmetic outcome. Fillet flap method of ear keloid repair and its cosmetic outcome: our experience